Corporate Entrepreneurship Traits in Family Businesses - Reményik , Bulcsú; Szántó , Peter; Papp-Váry, Árpád Ferenc (Journal of Ecohumanism, 2024)
Purpose – The purpose of this paper is to provide an overview of the current state of research of the relation of CE in FBs. It also examines future research opportunities in the field. Methodology/approach – A systematic review of literature was undertaken during the period of September 2021 and January 2022. According to Scopus, out of the 98 relevant articles to Family Business and Corporate Entrepreneurship published in a span of 22 years (1999-2021), the first appeared in academic research in 1999. In the approach they were searched using related keywords and specific selection criteria. Findings – There is a huge gap between CE and FB literature. Generalization cannot be undertaken due to the fact that most of the research focuses on (very) small businesses, while SMEs play a major role in the global economy. Originality/value – By identifying FB and CE as connecting antecedents, this paper suggests that their interconnection shall be further investigated and that the entrepreneurial effect is relevant in FBs.